The standardized Ginkgo biloba extract Egb-761 protects vascular endothelium exposed to oxidized low density lipoproteins - Pierre, S. V.; Lesnik, P.; Moreau, M.; Bonello, L.; Droy-lefaix, M. T.; Sennoune, S.; Duran, M. J.; Pressley, T. A.; Sampol, J.; Chapman, J.; Maixent, J. M. (Cellular and Molecular Biology, 2008)
Dietary antioxidants are frequently proposed as protective agents for the vascular endothelium during the onset of atherosclerosis. This protection may occur at two distinct levels. First, they prevent oxidative modification of atherogenic lipoproteins (LDL). Second, they can provide a cellular protection against oxidized LDL-mediated endothelium dysfunction, although this mechanism remains poorly considered in many instances. To gain insight into the mechanism underlying such cellular protection against oxidized LDL, we examined the impact of a popular traditional medicine, an extract from Ginkgo biloba with well-known antioxidant properties, on two endothelial cells properties: cell adhesion and ionic homeostasis. Cellular lipoperoxides levels were also measured as a marker of cellular oxidative stress. Human umbilical-vein endothelial cells were exposed to native (nat-) or oxidized (ox-) LDL, the latter prepared to be compatible with clinically observed levels of oxidation. Although nat-LDL had little effect, ox-LDL increased endothelial adhesive properties (35%, p<0.01) and lipoperoxidation (45%, p<0.01). Na,K-ATPase activity, a key regulator of ionic homeostasis, was significantly decreased after exposure to nat-LDL (30%, p<0.01) and dramatically depressed after exposure to ox-LDL (65%, p<0.001). The standardized preparation of Ginkgo biloba EGb-761 totally protected adhesive properties and endothelial lipoperoxide levels. Moreover, it limited the decrease in Na,K-ATPase activity induced by ox-LDL to levels similar to nat-LDL. This suggests that EGb-761 protects endothelial adhesive properties and helps prevent the disruption of ionic homeostasis. The EGb-761-mediated inhibition of ox-LDL-induced lipoperoxide levels in endothelial cells appears to be an important mechanism by which Ginkgo biloba extract protects endothelial properties.